Imagining a sustainable city to undo the path of colonial planning (REVISTA NODO, 2019)
It seems that Bookchin, like Mumford, or even non urban planning thinkers such as Marcuse, Gorz or Illich himself, knew how to coherently anticipate the present scenario by condemning the fate of the city half a century ago. It was not by chance that his thinking crossed borders with the ecological thinking that emerged in those years, as well as with the criticism of Marxism that would give rise to political ecology. All agree in one way or another on the need to rethink cities as a broader territorial, social and symbolic scenario. These thinkers, among others, were branded as extreme, skeptical and even anti-progressive, and saw the city’s decline as a whole. Others like Lefebvre recognized the exclusive centrality that the city was acquiring and sentenced the definitive disappearance of the countryside, advocating for a generalized right to the city. This overlooks, however, what Bookchin was so clear about: the bourgeois city, as a project and realization of the modern ideology of indefinite progress and based above all on economic growth, carries the germ of its own decadence. In addition, the poststructuralist and postmodern perspective of Soja opens up more complex and comprehensive horizons of understanding. And the developments of the decolonial theory, which discovers the intrinsically colonial nature of the Latin American city, places its birth in the same conquest of Abya Yala and allows us to understand its path from new points of reference. Thus, both in its theoretical formulation and the subsequent factual project, the Latin American city is reinterpreted as a mechanism (one more) of the coloniality of power that closed for five centuries the possibility of imagining other urban orders. But the finality represented by the climate crisis, the ineffable cultural dynamics of cities and the emergence of subaltern identities open up new horizons for thinking about their future, which is now in a new position.
Keywords: Urbanism; Modernity; Coloniality; Community; Participation